Landbruget og den nationale udvikling i Nordslesvig. En diskussion af Gottlieb Japsens tese - Vollertsen, Nils; Schultz Hansen, Hans; Stendal Pedersen, Finn; Østergård, Uffe; Fink, Jørgen (Historie/Jyske Samlinger, 1991)
-